Methodologische Probleme in der phonetischen Forschung des Polnischen als Fremdsprache - Alicja Derych (Linguistische Treffen in Wrocław)
The present paper is concerned with the methodology of phonetic research of Polish as a second/foreign language. Polish phonetics is approached here from the perspective of methodological problems that may be encountered during the study conduction. There exists a number of methodological approaches to this kind of studies, not so many comprehensive ones though (apart from e.g. Zaśko-Zielińska/Majewska-Tworek/Śleziak/Tworek 2020). The aim of the article was to signal issues that may be met by the researchers attempting to design their studies: selecting a study group meeting specific criteria, determining their language proficiency level, proposing adequate source materials, and planning the recording phase. The analysis was inspired by the study conducted during the preparation of a PhD dissertation on realisation of Polish consonants by native speakers of German. Material examples presented come from the recordings made for this purpose at the University of Leipzig in 2023. Due to a relatively less number of methodological guidelines dedicated to phonetic research of Polish as a second/foreign language, the author, having encountered some challenges during both assemblance of the study group and data collection, shared her reflections exemplified in the doctoral study along with some others which may emerge in similar research. The paper shows that phonetic studies concerned with Polish as a foreign/second language trigger methodological issues which relate to, apart from problems of equipment and data processing, the assessment of proficiency of the respondents, linguistic proficiency itself (especially related to orthography and vocabulary) and requirements in source material design, as well as study design (its temporal aspects), personal, extralinguistic factors, communicative situation and the role of the researcher in it, and the question of spontaneity closely linked to the textual type of the samples collected. The analysis may serve as a starting point both at the stage of planning one’s research, and evaluation of specific problems that were already encountered.